2018
DOI: 10.1039/c8nj02087f
|View full text |Cite
|
Sign up to set email alerts
|

Metallic 1T-MoS2 with defect induced additional active edges for high performance supercapacitor application

Abstract: Influence of thiourea on the formation of active-edges and the metallic phase of MoS2 and investigation of its energy storage properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…27,28 A new peak appeared at a low angle of 2q ¼ 7.26 , corresponding to the (001) crystal plane, with Na + insertion to form Na x MoS 2 . 29,30 The characteristic peak intensity of 1T@2H MoS 2 is lower than that of molybdenite concentrate, indicating the synergistic effect of hydrazine and sodium hydroxide expanded successfully natural molybdenite. 20,31 The XRF test (Table S3 †) further veried that aer the expansion of molybdenite concentrate, the content of Mo and S elements increased signicantly, while other impurities decreased greatly.…”
Section: Resultsmentioning
confidence: 98%
“…27,28 A new peak appeared at a low angle of 2q ¼ 7.26 , corresponding to the (001) crystal plane, with Na + insertion to form Na x MoS 2 . 29,30 The characteristic peak intensity of 1T@2H MoS 2 is lower than that of molybdenite concentrate, indicating the synergistic effect of hydrazine and sodium hydroxide expanded successfully natural molybdenite. 20,31 The XRF test (Table S3 †) further veried that aer the expansion of molybdenite concentrate, the content of Mo and S elements increased signicantly, while other impurities decreased greatly.…”
Section: Resultsmentioning
confidence: 98%
“…The d-spacing is 0.64 nm and ascribed to the (002) plane. 40 Obviously, the defects were generated at the edge sites and instantly inuenced the reduction of the charge transfer resistance in the electroactive material, which may be helpful to improve the charge storage capacity. It was conrmed that the CTAB-assisted MoS 2 nanoower morphology was more signicant due to the CTAB surfactant effect, which established that the high active edges improves the surface area as a result.…”
Section: Hr-tem Image Analysis Of Mos 2 Nanosheets and Mos 2 Nanoowermentioning
confidence: 99%
“…It has been proved that vacancy defects can promote electrochemical charge transfer achieving good conductivity and rate performance, because another additional defect level would be generated in the bandgap. [114][115][116] A number of fascinating state-of-the-art works have been reported. For example, Cao et al reported ultra-small oxygen vacancy-rich Co 3 O 4 /graphene composites with ultra-high-rate performance.…”
Section: Highly-active-site Electrode Materialsmentioning
confidence: 99%